A NOVEL INTEGRON IN THE GENOME OF ESCHERICHIA COLI ISOLATED FROM INDONESIAN MONITOR LIZARD (VARANUS SPP). - ESTI PUSPITASARI; ANTONIUS SUWANTO; AMARILA MALIK; WALTER ERDELEN (BIOTROPIA, 2001)
The genotype of antibiotic resistance  in natural isolates of Escherichia coli was determined  through integron detection and  characterization of the associated antibiotic  resistance. E. coli SG2 isolated from Varanus salvator  of Java demonstrated  resistance  to spectinomycin (50ng/ml)  and streptomycin (SOng/ml). Integron detection indicated  that eight isolates out of nine E. coli  isolates possessed a conserved segment of the integron. Amplification of  the inserted cassette of the integron in this SG2 isolate yielded a 1-kb DNA fragment. Sequence analyses indicated that this fragment was homologous with aad gene, which confirmed  the resistance  to spectinomycin/streptomycin. This is the first report on the presence of integron in the E. coli isolated from the environment. Key words: Integron / antibiotic resistance / Escherichia coli